The Effect of High Intensity Focused Ultrasound Combined with Ethanol on the Lesion of Porcine Liver in Vitro - HU DONG; GANG LIU (Iranian Journal of Medical Physics, 2022)
Introduction: As a non-invasive method of tumor hyperthermia, high intensity focused ultrasound (HIFU) has been widely used in the treatment of various solid tumors in recent years. The purpose of this study was to investigate the effect of HIFU combined with ethanol on biological tissue lesions. Material and Methods: Firstly, 0.5ml 95% ethanol was injected into the porcine liver tissue in vitro, then HIFU was used to irradiate the porcine liver. The B-mode ultrasound and needle hydrophone were used to monitor the cavitation. A thermocouple was also used to measure the real-time focal temperature. The ultrasonic signal scattered at the focal point of HIFU irradiation was collected by the fiber hydrophone, and the attenuation coefficient was calculated. Finally, the attenuation coefficient was input into the Khokhlov-Zabolotskaya-Kuznetov (KZK) equation and combined with the Pennes equation. The thermal lesion of the porcine liver was simulated by MATLAB software. Results: The length of the long axis of the lesion area simulated by the attenuation coefficient of cavitation was closer to the length of the long axis of the actual measured lesion area with ethanol injection, but the length of the short axis of the simulated lesion area was smaller than that of the measured lesion area. However, the length of the long axis of the lesion area simulated by the attenuation coefficient of cavitation was larger than the length of the long axis of the lesion area simulated by the attenuation coefficient of liver at room temperature. The same results were obtained for the length of short axis. Conclusion: HIFU combined with ethanol can produce larger lesions to biological tissues and improve the therapeutic effect.